Microbial Contamination on Used Surgical Masks among Hospital Personnel and Microbial Air Quality in their Working Wards: A Hospital in Bangkok - Pipat Luksamijarulkul; Natkitta Aiempradit; Pisit Vatanasomboon (Oman Medical Journal, 2014)
Objective: To assess the relationship of bacterial and fungal contamination on used surgical masks worn by the hospital personnel and microbial air quality in their working wards.